Caracterização funcional e estrutural de elementos transponíveis (hAT) encontrados nos genomas de espécies de drosophila - Bernardo, Larissa Paim (2017)
Transposable elements (TEs) are DNA sequences present in almost all organisms with the genome sequenced and its main characteristic is the capability of mobilization. This mobilization usaly causes negative effects to host, leading to elimination process as the main defence of hosts. However, the presence of TEs may also represents adaptative advantages, resulting in the maintance into host genomes with biological functions. The hAT superfamily of TEs is widely distributed in plants, animals and fungi. However, even being one of the most studied TEs superfamily, activity and interaction analyses of these TEs with host genomes are still scarce. Thereby, our general objective in this work was to contribute with the knowledge of estructural, functional and evolutive processes of hATs elements (hobo and Herves-like) present in Drosophila species, as well as investigate the role of minissatellites in the D. willistoni howilli1 element. This thesis is divided into three chapters. The first chapter have the specific aim of review the studied TEs in the literature covering issues such as classification, evolution and function of TEs, as well as present the thesis general and specific objectives. The second chapter intended to show our results and it is divided into three articles: the first one shows the analysis of hobo element evolutive scenario in Drosophila species using as markers TPEs repeats; the second article consists in the characterization of minisatellites found in the howilli1 element as potentials generators of miRNAs; the last article analyzes the distribution of Herves-like elements into Drosophila genomes. The third and last chapter consists in general discussions and perspectives.